Systematic study of the (n, 2n) reaction cross section for 121Sb and 123Sb isotopes. (1st May 2022) - Singh, R. K.; Singh, N. L.; Chauhan, R. D.; Mehta, Mayur; Suryanarayana, S. V.; Makwana, Rajnikant; Nayak, B. K.; Naik, H.; Nag, Tarak Nath; Katovsky, K.
Abstract: The cross sections of the 121 Sb 120 Sb m and 123 Sb 122 Sb reactions were measured at 12.50, 15.79 and 18.87 MeV neutron energies relative to the standard 27 Al 24 Na monitor reaction using neutron activation and offline γ-ray spectrometry. Irradiation of the samples was performed at the BARC-TIFR Pelletron Linac Facility, Mumbai, India. The quasi-monoenergetic neutrons were generated via the 7 Li reaction. Statistical model calculations were performed by nuclear reaction codes TALYS (ver. 1.9) and EMPIRE (ver. 3.2.2) using various input parameters and nuclear level density models. The cross sections of the ground and the isomeric state as well as the isomeric cross section ratio were studied theoretically from reaction threshold to 26 MeV energies. The effect of pre-equilibrium emission is also discussed in detail using different theoretical models. The present measured cross sections were discussed and compared with the reported experimental data and evaluation data of the JEFF-3.3, ENDF/B-VIII.0, JENDL/AD-2017 and TENDL-2019 libraries. A detailed analysis of the uncertainties in the measured cross section data was performed using the covariance analysis method. Furthermore, a systematic study of the reaction cross section for 121 Sb and 123 Sb isotopes was also performed within 14–15 MeV neutron energies using various systematic formulae. This work helps to overcome discrepancies in Sb data and illustrate a better understanding of pre-equilibrium emission in the reaction channel.